Implementation of Quality of Service (QoS) with Traffic Shaping Method in Wireless Internet Area as Network Optimization - Garno Garno; Dadang Yusup; Arip Solehudin; Agung Susilo Yuda Irawan; Jamaludin Indra (SYSTEMATICS, 2020)
This research is engaged in wireless internet networking. Wifi-based area internet service providers with a fairly large number of customers require extra services to keep customers subscribed to the internet. The problem that always appears as a job is the unstable quality of the internet to customers. A lot of customers and concurrently, when internet access is often a connection down and often have a hank on the router. All this is due to network management that is not regulated in such a way that is unstable. This study proposes the application of quality of service with traffic shaping techniques as a form of wireless internet network management. To find out the results, the study conducted a test before the method was applied, and the test after the method was applied. The results of the test data indicate that there are differences in the quality of the wireless network, and with the implementation of the traffic shaping method, the quality of the wireless internet network is more stable and reliable by customers even when traffic is very congested.